Solidarity management: a case analysis of digital transformation and its implications on the strategies and processes of a social development secretary - Santos, Dhyemis Santana dos (Brazilian Journal of Production Engineering, 2023)
Digital transformation has been a significant catalyst for the automation of tasks and managerial processes. Through the use of software, digital marketing, and media, systems were developed and implemented in a social development department to enhance processes and facilitate the development of strategies, allowing teams to focus on training, talent management, and expansion, thus improving organizational performance. Digital marketing provided opportunities to increase brand awareness, expand the target market, and consequently, enhance productivity. On the other hand, digital media enabled an increase in program engagement, facilitating monitoring and result evaluation. To achieve the goal of analyzing the impact of digital technology implementation, a qualitative-quantitative case study was conducted, focusing on the analysis of the benefits and challenges of digital technology implementation. Through task automation, significant improvements in organizational performance were achieved. This study contributes to understanding the role of digital technologies in management and identifying best practices and solutions.